2010
DOI: 10.1159/000285780
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Replacement Reverses Olanzapine-Induced Weight Gain and Hepatic Insulin Resistance in Ovariectomized Diabetic Rats

Abstract: Objectives: We investigated whether estrogen replacement modulated energy and glucose metabolic changes induced by olanzapine (OZP) and risperidone (RPD) in 90% pancreatectomized diabetic rats, some of whom had also been ovariectomized (OVX) and some of whom had not (sham). Methods: OVX diabetic rats were subcutaneously injected with estrogen replacement (17β-estradiol, 30 µg/kg/day) or a vehicle. Each group was divided into 3 subgroups, and each subgroup was orally either given a placebo, RPD (0.5 mg/kg body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 72 publications
1
5
1
Order By: Relevance
“…However, the fact that lipogenic gene expression levels were lower in OVX than in sham rats argues against the validity of this explanation, at least with regard to the whole set of metabolic alterations of OLZ. Notably, the effect of OLZ in OVX rats has been examined previously, but contrary to our findings, OLZ treatment was reported to induce hyperphagia and weight gain in OVX rats ( Park et al, 2010 ). However, the previous study was carried out on a diabetic background (90% pancreatectomy) in rats fed a high-fat diet, whereas here we used nondiabetic Sprague-Dawley rats fed standard chow.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the fact that lipogenic gene expression levels were lower in OVX than in sham rats argues against the validity of this explanation, at least with regard to the whole set of metabolic alterations of OLZ. Notably, the effect of OLZ in OVX rats has been examined previously, but contrary to our findings, OLZ treatment was reported to induce hyperphagia and weight gain in OVX rats ( Park et al, 2010 ). However, the previous study was carried out on a diabetic background (90% pancreatectomy) in rats fed a high-fat diet, whereas here we used nondiabetic Sprague-Dawley rats fed standard chow.…”
Section: Discussioncontrasting
confidence: 99%
“…The gender difference observed in this study may be explained by sex hormones. Mechanism research have found that sex hormones can upregulate insulin receptor expression and increase receptor phosphorylation protein kinase levels, thereby enhancing insulin signalling and preventing NAFLD 30 31. Furthermore, some sex hormones and their derivatives are strong endogenous antioxidants, which can inhibit the production of lipid peroxides in the liver and reduce its concentration, and play a protective role in the liver 32.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models have demonstrated an effect of estrogen on AP-mediated accumulation of adipose tissue, changes in feeding and glucose homeostasis, in ovariectomized rats treated with olanzapine [35,46,112,113]. For example, the AP sulpiride, like olanzapine, has been observed to cause weight gain in female, but not male rats [114].…”
Section: Resultsmentioning
confidence: 99%